Carbonic anhydrase inhibition by 1-aroyl-3-(4-aminosulfonylphenyl)thioureas. (December 2014) - Saeed, Aamer; al-Rashida, Mariya; Hamayoun, Mehwish; Mumtaz, Amara; Iqbal, Jamshed
Abstract A series of 1-aroyl-3-(4-aminosulfonylphenyl)thioureas containing free sulfonamide group has been evaluated for their ability to inhibit bovine carbonic anhydrase II (bCA, EC 4.2.1.1). All compounds in the series were able to inhibit bCA II, the most active inhibitor had IC50 value of 0.26 ± 0.01 µM. Molecular docking studies and detailed structure–activity relationship studies were carried out. The absorption, distribution, metabolism, excretion (ADME) properties, as a predictor of oral absorption, were computationally calculated and compared with the clinically used drug acetazolamide.